THE EXPLORATION OF PERLOCUTINARY ACTS IN KINGSMAN: THE GOLDEN CIRCLE FILM SCRIPT - NICHOLAS FERNANDO; VIVI NOVALIA SITINJAK; NURLAIDY JOICE SIMAMORA (LINGUISTICA, 2024)
Using descriptive qualitative research, this study investigates the perlocutionary acts found in the film script of the 2017 film Kingsman: The Golden Circle by  Matthew Vaughn. The objectives of this study are to explain the types and the context of the perlocutionary acts found in the dialogues of the film script. Pragmatic approach is applied and a total sum of 10 data in form of dialogues were found, which were categorised based on Searle’s 1969 Speech Act theory. Furthermore, the context of situation of all the data were explained with the basis of pragmatic approach supported by Yule’s theory 1996. Miles & Huberman’s theory (1994) is assigned in analyzing the data. Thus, this study concluded that the five types of Perlocutionary Acts appear in the film script, with Directives acts to appear most often, followed by Assertives, and finally Commissives, Expressives and Declaratives. However, the reader must have a deep understanding in context of situation to understand the meaning of the text. This study contributes to give a new insight in perlocutionary acts based on context of situation. Authors suggest to futher researcher to analyze perlocutionary act in gender context and to apply context of situation in avoiding misinterpretation and misact.